PENERIMAAN PEMANGKU KEPENTINGAN KABUPATEN DALAM PENGEMBANGAN PELAYANAN TERPADU PRA-KONSEPSI - Matsna Haniifah; BJ Istiti Kandarina; Retna Siwi Padmawati (Journal of Health Service Management, 2021)
Background: Stunting prevention can be accomplished in prewedding services for prospective brides based on the latest regulations regarding the acceleration of stunting reduction. Sleman Regency, as one of the focus locations for the intervention of stunting, has institutions that are involved in the service of prospective brides, i.e. institutions in the field of health, religion, and family planning. This new policy is a challenge because the existing programs in these institutions have not utmostly directed the prevention of stunting. There is a suggestion from the academic side to develop pre-conception integrated services causes be necessary to explore the early acceptance of Sleman Regency stakeholders. Objective: This study aimed to explore the potential in Sleman Regency to develop the pre-conception integrated services, including the early acceptance of stakeholders. Methods: A qualitative approach with a descriptive-exploratory design is used in this study by determining subject by purposive sampling. Research was conducted in Sleman and Mlati Sub-district. Data collection using in-depth interviews, focus group discussions, observation and document studies using the framework analysis method as a technique in analyzing the data. Results: There are various things behind aspects of stakeholder acceptance, i.e. capacity in the aspect of affective attitudes, the aspect of supportive needs of each stakeholder group, various things that affect the financing aspect, aspects of effectiveness perceived by stakeholders, aspects of stakeholder confidence in participating, and aspects of suitability of the proposed concept with stunting reduction. Conclusion: Stakeholders give a positive response and confidence to participate in pre-conception integrated service. In the future, local governments need to provide policy support to implement pre-conception integrated services as commitment to preventing stunting from upstream. In addition, stakeholders can maximize potential so that pre-conception integrated services can be a solution in improving health status of community.